(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. We aimed determine the impact of an 8-week intradialytic exercise program, consisting of 15 minutes of cumulative duration low-intensity exercise during the first 2 hours of dialysis on serum electrolytes levels and hemoglobin. Materials and Methods. In a randomized controlled trial of in an outpatient hemodialysis unit, clinically stable hemodialysis patients (n = 47) were included and assigned into the aerobic exercise group (n = 25) and the control group (n = 23). Aerobic exercises were done in groups, 15 min/d, 3 times a week, for 2 months. The main outcome measures were biochemical variables including serum levels of calcium, phosphate, and potassium levels and hemoglobin level. Results. After an 8-week intervention, significant improvements were seen in serum phosphate levels (decreased by 1.84 mg/dL) and serum potassium levels (decreased by 0.69 mg/dL). No side-effects were observed. Serum calcium and hemoglobin levels did not change significantly in the exercise group. Conclusions. A simplified aerobic exercise program is a complementary, safe, and effective clinical treatment modality in patients with end-stage renal disease on dialysis.